Examining gendered pathways in the causal chain linking neighborhood navigational strategies and unstructured socializing to adolescent violent offending. (September 2016) - Zimmerman, Gregory M.
Abstract: Purpose: Research has demonstrated that adolescents with higher levels of street efficacy – the perceived ability to avoid violence and to stay safe in the neighborhood – are less likely to engage in violence themselves. But, empirical research has yet to examine sex differences in the relationship between street efficacy and violent offending. This study examines whether the causal chain linking street efficacy to adolescent violent offending is gendered. Methods: Using data from the Project on Human Development in Chicago Neighborhoods, a three-level logistic item response model nested 14, 483 violent crime item responses within 1817 subjects representing 222 neighborhoods across metropolitan Chicago. Results: An attenuated sex gap in violent offending was observed at higher levels of street efficacy. This was accounted for by: (1) reductions in the sex gap in unstructured socializing at higher levels of street efficacy, and (2) a concomitant effect of unstructured socializing on violent offending. Conclusions: Street efficacy and unstructured socializing matter in the etiology of youthful offending, but the ways in which these constructs are relevant are nuanced. In particular, gender has a strong impact on the development and manifestation of street efficacy and unstructured socializing, which, in turn, are related to violent offending. Highlights: The impact of street efficacy on violence is attenuated among female youth. The sex gap in unstructured socializing is reduced as street efficacy increases. The process linking street efficacy, unstructured socializing and crime is gendered.